Prompt Engineering and Input Art as a Lever for Knowledge Productivity in the Era of Generative Artificial Intelligence: An In-depth Analytical Study in Light of the Latest Experimental Studies and Human-Machine Integration Models - Aljonied, Sakher farea Ghaleb (Journal of Business Administration and Strategy, 2026)
This study investigates the structural transformations in the concept of personal productivity for knowledge workers in light of the increasing dominance of Large Language Models (LLMs), with a particular focus on the "Art of Input" and "Prompt Engineering" as a cognitive competence and an intermediary technical skill. The research stems from the problem that the gap between the algorithmic capabilities of artificial intelligence and the tangible actual outputs is mainly attributed to a deficiency in the human user's "context engineering." Through a descriptive analytical methodology based on a critical review of the latest experimental studies and research reports, the study concluded that mastering advanced prompt engineering techniques leads to overcoming what is known as the "jagged technological frontier," achieving qualitative leaps in output quality and speed of accomplishment, especially among less technically skilled groups (Wharton School, 2025). The research also provides a scientific framework for integration models (Centaur & Cyborg) as future operating frameworks, recommending the necessity of integrating input art as a fundamental skill in academic curricula and professional development programs.